(untitled) (Research, Society and Development, 2020)
The disordered consumption of water has been aggravating the maintenance and improvement of the capture, treatment and distribution services for society. According to the São Paulo State Government Secretariat of Sanitation and Water Resources (2015), water is a renewable resource, but limited and of high economic value, and its scarcity can occur due to climatic, hydrological conditions or excessive demand. The increase in consumption has been demanding alternatives to capture each day farther from consumption centers, which is increasing costs, making it difficult and aggravating the maintenance and improvement of treatment services. This article aimed to study the separation of water used in showers and sinks for reuse and application in buildings and condominiums. A study on the economic potential of treated water obtained through the use of gray water is presented. In function of the objectives, a research with exploratory and qualitative characteristics was applied. In addition to the environmental benefits, the results with the implementation of the system in homes, may provide a reduction of sewage for the utility by 30%. The total cost of materials for deployment in a building with up to 16 apartments was estimated at R 5,650.32.